The President, office and powers, 1787-1957 : history and analysis of practice and opinion - Corwin Edward S. (James Stokes lectureship on politics, 1957)
Primarily a study in American public law with an approach partly historicial, partly analytical, and critical. The central theme is the development and contemporary status of presidential power, and of the presidential office under the Constitution